The age, growth, and maturation of the spiny dogfish, Squalus acanthias L., of the northwest Atlantic - Marine Sciences Research Center; Slauson, T. P.; Woodhead, P. M. J.; Castaneda, R. E. (Marine Sciences Research Center, Stony Brook University, 1983)
v, 44 p. : ill., map 28 cm. Bibliography. from the abstract, "The spiny dogfish is the largest under-utilized resource of the northeastern fisheries of the U.S., yet little critical data is available on its biological parameters. This study describes the age-length relationships, growth and maxinrurn size for both males and females; estimates were also made of size at reproductive maturation. Dorsal fin spines were used to detennine the age of fish. The samples for data development were collected in 1976, 1979, 1980, and 1981 at sites in the Gulf of Maine and the New York Bight. . ." The works contained within this collection are the final products of a joint collaboration between the School of Marine and Atmospheric Sciences (SOMAS); the MASIC Library and the Preservation Department. The project was conducted during the winter through summer 2013 academic semesters, and its focus was to convert older, archival records generated by SOMAS and maintained within the University Libraries to accessible, electronic resources in support of research and learning. All works are based on the original, analog (paper) records as released by SOMAS, except where born digital only records have been loaded to the system. All works have been preserved for historic purposes, please see the Marine and Atmospheric Sciences Library for assistance in viewing the analog originals upon which this project is based.